Choosing and using Drosophila models to characterize modifiers of Huntington's disease. (20th July 2012) - Green, Edward W.; Giorgini, Flaviano
Abstract : HD (Huntington's disease) is a fatal inherited gain-of-function disorder caused by a polyQ (polyglutamine) expansion in the htt (huntingtin protein). Expression of mutant htt in model organisms is sufficient to recapitulate many of the cellular defects found in HD patients. Many groups have independently developed Drosophila models of HD, taking advantage of its rapid life cycle, carefully annotated genome and well-established molecular toolkits. Furthermore, unlike simpler models, Drosophila have a complex nervous system, displaying a range of carefully co-ordinated behaviours which offer an exquisitely sensitive readout of neuronal disruption. Measuring HD-associated changes in behaviour in Drosophila therefore offers a window into the earliest stages of HD, when therapeutic interventions might be particularly effective. The present review describes a number of recently developed Drosophila models of HD and offers practical guidance on the advantages and disadvantages of various experimental approaches that can be used to screen these models for modifiers of mutant htt-mediated toxicity.